The Islamic Education Methods in Al-Quran - Kemas Abdul Hai (Ta'dib: Jurnal Pendidikan Islam, 2017)
When the Prophet Muhammad was appointed as an apostle, the first commandment from Allah to him was to read, because reading is a symbol towards the mastery of science. As an educator of the Messenger of Allah, whatever he does is guided directly from Allah SWT through the verses revealed to him (al-Qur'an). His success in educating humanity is the background of this essay. That is by looking from the Qur'an as information and references used in the Prophet Muhammad SA in educating people. In this article, I described the three global principles in defending (educating) through the Qur'an Surah an-Nahl verse 125 consisting of the al-Hikmah, al-mau'izah al-hasanah, and al-mujadalah. I also discussed the method of these three principles that the Prophet Muhammad has made as the best example in educating humanity. Its success is not only recognized by Muslims but also non-Muslims.